A Sobering Look at Treatment Effectiveness of Military-Related Posttraumatic Stress Disorder. (July 2022) - Levi, Ofir; Ben Yehuda, Ariel; Pine, Daniel S.; Bar-Haim, Yair
Approximately two thirds of veterans with posttraumatic stress disorder (PTSD) remain with the disorder following treatment. Pinpointing the per-symptom effectiveness of treatments in real-world clinical settings can highlight relevant domains for treatment augmentation and development. Baseline and posttreatment assessments of PTSD and depression were performed in 709 veterans with PTSD. PTSD remission was 39.4%. Treatment was least effective for intrusion symptoms and had no effect on flashbacks or on poor recall of traumatic features. Of veterans who remitted, 72.8% still met diagnostic criteria for at least one cluster. Poor clinical effectiveness was noted for depression; only 4.1% of the patients remitted following treatment. Treatments for veterans with PTSD show limited overall effectiveness in real-world settings. Enhancing treatment response may require enhancing provider fidelity and patient compliance with extant treatments or the development of new treatments that specifically target the symptoms of PTSD that do not respond well to extant treatments.